2020
DOI: 10.6061/clinics/2020/e2414
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Overnight Wireless High-Resolution Oximeter plus Cloud-Based Algorithm for the Diagnosis of Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) is a common but largely underdiagnosed condition. This study aimed to test the hypothesis that the oxygen desaturation index (ODI) obtained using a wireless high-resolution oximeter with a built-in accelerometer linked to a smartphone with automated cloud analysis, Overnight Digital Monitoring (ODM), is a reliable method for the diagnosis of OSA. METHODS: Consecutive patients referred to the sleep laboratory with suspected OSA underwent in-laboratory polysomnography (PSG) and simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 28 publications
2
24
0
4
Order By: Relevance
“…Other studies have identified similar values for specificity, but reported the sensitivities of 42.0% ( 14) and 80.0% (15) for detecting mild apnea using ODI (compared to PSG type I). For moderate apnea, we found the same sensitivity as that for mild apnea (66.7%); however, specificity was slightly lower (85.3%) and in an intermediate range compared to the reports in the literature (69.1 to 95.1%) (14,15,20,26,29). For severe apnea, ODI sensitivity was 95.5% and specificity was 88.9%, similar to previously reported studies (14,15,20,29).…”
Section: ' Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Other studies have identified similar values for specificity, but reported the sensitivities of 42.0% ( 14) and 80.0% (15) for detecting mild apnea using ODI (compared to PSG type I). For moderate apnea, we found the same sensitivity as that for mild apnea (66.7%); however, specificity was slightly lower (85.3%) and in an intermediate range compared to the reports in the literature (69.1 to 95.1%) (14,15,20,26,29). For severe apnea, ODI sensitivity was 95.5% and specificity was 88.9%, similar to previously reported studies (14,15,20,29).…”
Section: ' Discussionsupporting
confidence: 87%
“…For moderate apnea, we found the same sensitivity as that for mild apnea (66.7%); however, specificity was slightly lower (85.3%) and in an intermediate range compared to the reports in the literature (69.1 to 95.1%) (14,15,20,26,29). For severe apnea, ODI sensitivity was 95.5% and specificity was 88.9%, similar to previously reported studies (14,15,20,29). Evaluation of the degree of correlation to explain the variability of ODI in relation to that of AHI revealed an r of 0.93 and R 2 of 86.17% (po0.05).…”
Section: ' Discussionsupporting
confidence: 68%
See 3 more Smart Citations